KATA-KATA TABU DALAM BAHASA INGGRIS DAN BAHASA SANGIHE : SUATU ANALISIS KONTRASTIF - WALUKOW, THEABELLA NATASHA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â This research is entitled â€œTaboo Words in English and Sangerese: A Contrastive Analysisâ€. The objectives of this research are to identify and classify the types of taboo words and to analyze the differences of taboo words in English and Sangerese.Â This research uses a descriptive method. There are three steps to finish this research, those are preparation, read the theory of sociolinguistics related to taboo words, get information through browsed internet about the taboo, and looked for previous thesis related to taboo. The second step is data collection, the data of taboo words in the English were taken from library research and previous researches; while in Sangerese were taken from native speakers in three vilages: Kauhis, Karatung I and Karatung II, subdistrict Manganitu, in Sangihe Island. The third step is to analyze the data that using the theory of Wardhaugh (1986:230) and were contrasted to find the differences using Lado theory.Â Â The results of this research shows that there are 53 taboo words found in Sangerese and they were classified into ten types those are: sex, bodily function, animal, death, excretion, curse, eating, fisherman, devil, and address terms. It also shows that the causes of using taboo words are to express the emotion, such as anger, happy, and surprises, to talk about sex, to joke, and to insult.Â Keywords: Taboo Words; English and Sangerese